2009
DOI: 10.1007/s11605-009-0930-7
|View full text |Cite|
|
Sign up to set email alerts
|

Obesity and Gastroesophageal Reflux: Quantifying the Association Between Body Mass Index, Esophageal Acid Exposure, and Lower Esophageal Sphincter Status in a Large Series of Patients with Reflux Symptoms

Abstract: IntroductionObesity and gastroesophageal reflux disease (GERD) are increasingly important health problems. Previous studies of the relationship between obesity and GERD focus on indirect manifestations of GERD. Little is known about the association between obesity and objectively measured esophageal acid exposure. The aim of this study is to quantify the relationship between body mass index (BMI) and 24-h esophageal pH measurements and the status of the lower esophageal sphincter (LES) in patients with reflux … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
96
2
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(116 citation statements)
references
References 29 publications
6
96
2
8
Order By: Relevance
“…This association was even more pronounced in males, and after adjustment for potential confounders, such as age, gender, and race, the observed associations of adiponectin with BE remained significant. Obesity is shown to be an independent risk factor of GERD23 through increased transient lower esophageal sphincter relaxation, which is an important mechanism of GERD 24. These results were compatible with our study, which demonstrated that weight and BMI was significantly high in Group III (severe GERD) in comparison to the control group.…”
Section: Discussionsupporting
confidence: 92%
“…This association was even more pronounced in males, and after adjustment for potential confounders, such as age, gender, and race, the observed associations of adiponectin with BE remained significant. Obesity is shown to be an independent risk factor of GERD23 through increased transient lower esophageal sphincter relaxation, which is an important mechanism of GERD 24. These results were compatible with our study, which demonstrated that weight and BMI was significantly high in Group III (severe GERD) in comparison to the control group.…”
Section: Discussionsupporting
confidence: 92%
“…An answer to this intriguing finding remains unclear. We speculate that because patients with high BMI are diagnosed with GERD more often than those with low BMI, [19][20][21][22][23] patients with high BMI are more likely to undergo endoscopic surveillance and this could result in the diagnosis of early EC. Lagergren et al 11 reported an odds ratio of 7.7 for EAC among patients with GERD symptoms compared with individuals without GERD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a large cohort of patients with foregut symptoms, the prevalence of a mechanically defective LES (based on hypotensive LES, total length, or abdominal length) increased as BMI increased, with 55% of obese patients demonstrating a defective LES [17] . While nearly 30% of the 1659 subjects in this study were noted to be obese, specific data regarding severely obese individuals were not described.…”
Section: Pathophysiologymentioning
confidence: 94%
“…The latter is a key step in the development of hiatal hernia, which, based on endoscopic evidence, is more prevalent in obese individuals than normal weight individuals [27,28] . Indeed, the negative effects of the presence of hiatal hernia on LES function might in fact be greater than the effects of obesity per se [17] .…”
Section: Pathophysiologymentioning
confidence: 99%